Origem e distribuição da artéria celíaca de avestruzes (Struthio camelus) - Vasconcelos, Bruno Gomes (2011)
The exploration of ostriches is aimed at marketing the meat, feathers, leather and fat. Closely related to productivity is the digestive system, and among the major vessels responsible for nutrition is the celiac artery that was studied the origin and distribution. In 30 specimens, the left isquiatic artery was cannulated for injection of a marker of blood vessels then were fixed in formalin solution 10% by deep intramuscular applications, subcutaneous and intracavitary. We concluded that it originated from the descending aorta, its first branch ventral and headed for the right antímero in its path sends branches to: esophagus, proventriculus, ventricle, spleen, liver, gallbladder, pancreas, duodenum, ileum, cecum left and right.